Intestinal invagination - Elizabeth Hernández Moore; Nancy Martínez Villavicencio; José Carlos Bueno Rodríguez; Neyda Delgado Marín; Carlos Morán Martínez; Dayamnelys Aguilar Atanay (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Intestinal intussusceptions are the most frequent cause of acute surgical occlusive syndrome in infants; it is idiopathic in more than 90% of cases. Their treatment can be conservative, with reduction by means of imaging and hydrostatic procedures, or surgical. We presented the Good Clinical Practices Guideline for Intestinal intussusceptions, approved by consensus in the 3th National Good Clinical Practices Workshop in Pediatric Surgery (Camagüey, Cuba; February 23 - 26, 2004).